Hai pafōmansu Python - Gorelick, Micha; Ozsvald, Ian (Orairī Japan, 2023)
"A guide to programming with Python, updated for Python 3, explores the fundamental theory behind design choices and offers a better understanding of Python implementation, covering such topics as locating performance bottlenecks, how Python abstracts the underlying computer architecture, and tools to compile Python down to machine code." --